Physical therapy intervention in the treatment of stress urinary incontinence (Research, Society and Development, 2021)
Urinary incontinence (UI) can have several causes for its manifestation in the body, such as different anatomical characteristics, neuromuscular problems and psychological problems, which exacerbate women's health. Stress incontinence is the most affected by women in different age groups. In relation to this, it happens because there is still no way to avoid daily physical or physiological efforts by the body. In this context, stress urinary incontinence is defined as any non-voluntary loss of urine during moments of coughing, physical activities, sneezing, as well as exercises that promote rapid movement of position. The objective of this work is to discuss the importance of the role of the professional physiotherapist in the care of women with stress urinary incontinence. The physical therapy resource such as kinesiotherapy is a positive treatment, as it enables the development and improvement of patients' quality of life. Another resource is the electrical stimulation that promotes, depending on its parameters suitable for the pathology, a significant improvement in the involuntary loss of urine. With this, the three resources being biofeedback, vaginal cones and electrostimulation become allies in the treatment and strengthening of the entire region and pelvic muscles. Finally, it is understood that the physiotherapist and its resources have a fundamental role in helping the treatment of patients with urinary incontinence, mainly to improve the quality of life and strengthen the pelvic floor, and bring back the comfort to be able to perform the tasks daily.